THE ROLE OF BIOCHEMICAL BLOOD ANALYSIS IN ACTIVITY VERIFICATION OF PULMONARY TUBERCULOSIS - KH.R. NASYRDZHANOVA; A.M. SABUROVA; U.YU. SIRODJIDINOVA; M.S. MAKHSUDOVA (Avicenna Tajik State Medical University, 2018)
Objective: To study the interconnection of inflammatory process of vessels endothelium with biochemical changes in verification of the pulmonary tuberculosis (PTB) diagnosis. Methods: Results of a study of 56 PTB patients are given in the age of 18-50 years, 26 of them with a drug-resistant (DR) form of PTB and 30 with a drug-sensitive (DS) form of PTB. The status of the vessels endothelium was judged by the amount of C-reactive protein (CRP), fibrinogen, and Willebrand factor. Results: The studies have shown a significant increase in the content of CRP (4.22±0.13), fibrinogen (4.21±0.21) and Willebrand factor (114.0±2.5) in patients with DR PTB. The received data indicate that the course of a specific process of patients of PTB with extensive DR is more severe than in patients with DS PTB. The DR PTB is accompanied by the development of the syndrome of a systemic inflammatory response, whose manifestation is interrelated with the severity of the patient's condition. The syndrome of a systemic inflammatory response is manifested by an increase in the blood serum of the C-reactive protein, fibrinogen, and Willebrand factor. The values ​​of CRP within 4-5 mg/l are an early indicator of the process activity. Conclusion: As a diagnostic test for PTB can be used to determine the status of endothelium blood vessels criteria for which are elevated levels of CRP, fibrinogen, and Willebrand factor.